2012
DOI: 10.1177/0960327111428630
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CYP1A1, GSTT1 and GSTM1 polymorphisms on the risk of lung cancer

Abstract: Lung cancer, which is mainly affected by environmental factors, is a lethal malignancy. It is also important to investigate the effect of genetic factors on lung cancer aetiology. In this study, we aimed to investigate the distribution of CYP1A1*2C, GSTT1 and GSTM1 polymorphisms in Turkish lung cancer patients to determine whether any promoting effect of polymorphisms could cause development of lung cancer. For this purpose, genomic DNA samples obtained from peripheral blood of 128 patients with lung cancer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 37 publications
(57 reference statements)
0
2
1
Order By: Relevance
“…In contrast, the results of previous studies among Turkish population demonstrated increased risks for developing ovarian and prostatic carcinomas (Aktas et al, 2002;2004) but no association was detected with lung cancer (Atinkaya et al, 2012). The results of our study also did not reveal an increased risk of BC for CYP1A1 Ile 462 Val variant genotype.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the results of previous studies among Turkish population demonstrated increased risks for developing ovarian and prostatic carcinomas (Aktas et al, 2002;2004) but no association was detected with lung cancer (Atinkaya et al, 2012). The results of our study also did not reveal an increased risk of BC for CYP1A1 Ile 462 Val variant genotype.…”
Section: Discussioncontrasting
confidence: 99%
“…However, individuals not exposed to these risk factors can also develop lung cancer, indicating that a difference in cancer susceptibility exists among individuals (Ada et al, 2012). Previous studies indicate that genetic polymorphisms in the glutathione S-transferase M1 (GSTM1) gene may affect the risk of lung cancer (Nakachi et al, 1993;Cao et al, 2004;Chen et al, 2004aChen et al, , 2012Atinkaya et al, 2012;Han et al, 2012;Li et al, 2012;Liang et al, 2012;Liu et al, 2012). Subjects who have inherited specific variants in the GSTM1 gene may be susceptible to the effects of chemical carcinogens and thus at a high risk of developing lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many investigators have reported association between CYP1A1 polymorphisms and cancers (Dai et al, 2009;Atinkaya et al, 2012;Lopez-Cima et al, 2012;Sergentanis et al, 2012;Ding et al, 2013), especially for two main functional polymorphic sites of CYP1A1 gene (MspI and Ile/Val) and cancer susceptibility. Previous studies (Kawajiri et al, 1990;Nakachi et al, 1991;Hayashi et al, 1992;Xu et al, 1996) have suggested that variant allele of CYP1A1 MspI polymorphisms is associated with malignancies, particularly lung cancer.…”
Section: Introductionmentioning
confidence: 99%